Do opinion leaders know more? Knowledge accuracy, self-confidence, and media use in agricultural issues - Andreas Gabriel; Vera Bitsch (PLoS ONE, 2026)
This empirical study examines the relationship between knowledge accuracy, self-confidence, and perceived opinion leadership in the context of agricultural issues. Using data from a representative online survey of the German population (n = 2,022), the study analyses how objective factual knowledge and subjective confidence are associated with individuals’ self-reported role as opinion leaders, with particular attention to confidence calibration and the Dunning–Kruger Effect (DKE). The theoretical framing integrates Social Cognitive Theory (SCT) and the Two-Step Flow of Communication Model (TSFCM) as heuristic perspectives for understanding social learning and information exchange, while explicitly acknowledging their limitations in contemporary media environments. Across nine factual knowledge statements, the average correct response rate was 64%, while a substantial share of respondents exhibited measurable overconfidence, particularly for false statements. Individuals classified as opinion leaders report significantly higher confidence levels and more intensive use of both, traditional and digital media than the general population, yet they do not demonstrate higher knowledge accuracy. Regression analyses show that confidence and media use are substantially stronger predictors of perceived opinion leadership than factual knowledge. These findings highlight a systematic mismatch between confidence and knowledge among influential communicators in an information-sensitive domain. Rather than demonstrating misinformation effects directly, the results point to the importance of confidence calibration and critical source evaluation in public communication on agriculture and food. The study contributes to the literature by empirically linking confidence miscalibration and opinion leadership within a general population context. From an applied perspective, the findings underline the relevance of targeted communication and literacy initiatives that address overconfidence among highly confident communicators.